CORRECTION OF STRESS-INDUCED DISORDERS OF THE HYPOTHALAMIC-PITUITARY-ADRENAL SYSTEM WITH MULTIPROBIOTIC "SYMBITER" - Falaleeva, T.M.; Virchenko, O.V.; Yankovski, D.S.; Beregova, T.V. (World of Medicine and Biology, 2012)
The excessive stress causes disorders of the hypothalamic-pituitary-adrenal system. It was established that multiprobiotic "Symbiter acidophilic concentrated" restores the functioning of this system, therefore provides favorable conditions for healing of stress-induced lesions in gastric mucosa of rats. Multiprobiotic influence on the stress-system is realised due to its immunomodulatory properties: it reduces the level of interleukin-1β in serum of rat blood, which is increasing in terms of stress.